Plasma cell granuloma of the oral cavity: a mucosal manifestation of immunoglobulin G4-related disease or a mimic? - Laco, Jan; Kamarádová, Kateřina; Mottl, Radovan; Mottlová, Alena; Doležalová, Helena; Tuček, Luboš; Žatečková, Kamila; Slezák, Radovan; Ryška, Aleš (Virchows Archiv, 2015)
The aim of the study was to test the hypothesis that oral plasma cell granuloma may represent a mucosal manifestation of immunoglobulin (Ig)G4-related disease (IgG4-RD) in the oral cavity. The study sample comprised two males and four females, aged 54-79 years (median 62 years). The lesions were localized on gingival/alveolar mucosa (four cases), hard palate, and floor of the mouth, measuring 17-40 mm (median 31 mm). The duration of the lesions ranged from 3 months to several years. Information on IgG4 serum levels was available for two patients, and these were increased to 1.85 and 1.65 g/L, respectively. The follow-up period ranged 11-30 months (median 13 months). None of the lesions recurred, and none of the patients developed any manifestation of IgG4-RD. Microscopically, all cases presented as nodular lesions composed of numerous polyclonal plasma cells admixed with lymphocytes, histiocytes, mast cells, and eosinophils, set within collagenized stroma in variable proportions. Obliterative phlebitis was observed in two cases. The number of IgG4-positive plasma cells ranged between 51 and 142 per HPF (median 114), while the IgG4/IgG ratio values ranged between 0.16 and 0.72 (median 0.44) and were above 0.40 in three cases. Based on international criteria, two cases were diagnosed as definite and one as probable IgG4-RD. Oral plasma cell granuloma is a heterogeneous group of lesions, and a subset may represent a mucosal manifestation of IgG4-RD in the oral cavity.
Keywords: senioři; diferenciální diagnóza; ústní sliznice; nemoci úst; Histiocytes; Mouth Mucosa; plazmatické buňky; mastocyty; Gingivitis; imunoglobulin G; Time Factors; eozinofily; nemoci imunitního systému; Middle Aged; mužské pohlaví; Immune System Diseases; Mouth Diseases; histiocyty; Eosinophils; Immunoglobulin G; ženské pohlaví; Humans; Plasma Cells; gingivitida; časové faktory; lidé středního věku; Diagnosis, Differential; Mast Cells; plazmocelulární granulom; Female; Aged; Granuloma, Plasma Cell; lidé; Male